Biodegradation of the Films of PP, PHBV and Its Blend in Soil - Goncalves, S. P. C. [UNESP]; Martins-Franchetti, S. M. [UNESP]; Chinaglia, D. L. [UNESP] (Springer/plenum Publishers, 2009)
Films of poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and poly(propylene) (PP), PP/PHBV (4:1), blends were prepared by melt-pressing and investigated with respect to their microbial degradation in soil after 120 days. Biodegradation of the films was evaluated by Fourier transform infrared spectroscopy, scanning electron microscopy, differential scanning calorimetry, and X-ray diffraction. The biodegradation and/or bioerosion of the PP/PHBV blend was attributed to microbiological attack, with major changes occurring at the interphases of the homopolymers. The PHBV film was more strongly biodegraded in soil, decomposing completely in 30 days, while PP film presented changes in amorphous and interface phase, which affected the morphology.
Keywords: Biodegradation; Blend; FTIR; DSC; X-Ray